PENGARUH PENGAWASAN DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI KANTOR BADAN LINGKUNGAN HIDUP KABUPATEN ROKAN HULU - Samura, Ibnu Sina; Rama, Rovanita; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the influence of Supervision and Working Environment on Employee Work Discipline Office of the Environmental Agency of RokanHulu. In this study, there are three variables: Supervision (X1), Working Environment (X2), and Work Discipline (Y). The population of this research is all employees working in the Office of the Environment Agency with a total sample of 38 people. This study uses linear regression with SPSS version 21. The results showed that the variables of Supervision, and Working Environment either simultaneously affect the Work Discipline Employees in the Office Environment Agency RokanHulu. Work Environment Variables become the most dominant factor in influencing Work Discipline Employees. Hope researchers in this study is the Office of the Environment Agency should Rokan Hulu can improve Supervision and Working Environment for employees so that they can continue to improve employee in the Office of Disciplinary Work Environment Agency Rokan Hulu. With that employees will feel heavy for leaving the company in order to better and more comfortable. It is intended that employees become more disciplined in work. In order to improve labor discipline employees of the Office of Environmental Agency of Rokan Hulu leaders must rise again oversight and reorganize work environment where employees to be better and convenient. Leaders also need to pay more attention and apply the correct working procedures and good sertamemberikan directives on employees so that each employee has a level kesaadaran to the job and apply kepadasetiap employees so that the employees more responsible in work.Keyword : Monitoring, Work Environment, Work Discipline.